Neonatal Hydrometrocolpos Secondary to Imperforate Hymen Presented with Acute Urinary Retention: Case Report - Tegene D; Assefa T; Edris A (Dove Medical Press, 2023)
Dereje Tegene, Tesfalem Assefa, Abdurahman Edris Department of Obstetrics and Gynecology, Adama Hospital Medical College, Adama, EthiopiaCorrespondence: Dereje Tegene, Tel +251913909665, Email fekadutd79@gmail.comBackground: Hydrometrocolpos is a rare clinical condition characterized by the accumulation of fluid or mucus secretions in the vagina and uterus due to distal vaginal obstruction. Imperforate hymen is the most common cause of congenital hydrometrocolpos. The diagnosis of congenital hydrometrocolpos can be made prenatally or postnatally. Imperforate hymen is generally managed by hymenotomy or hymenectomy.Case Presentation: This is a 26-day-old female neonate who was born from a 29-year-old Para − 3 mother after 9 months of amenorrhea. ANC follow-up was uneventful except her obstetric ultrasound scan at 36+3 weeks found a fetal lower intra-abdominal mass. Without proper postnatal evaluation, the neonate was discharged home with the mother after 12 hours of vaginal delivery. Currently, the neonate was referred to our hospital with the diagnosis of Acute Urinary retention, 2o Hydrometrocolpos, after having frequent crying, abdominal distension, and failure to pass urine of 2 days duration. On physical examination, there was a tender, cystic, and mobile mass palpable in the lower abdomen, and up to opening the labia there was a curved membrane covering the vaginal opening. Abdomino-pelvic ultrasound and Magnetic Resonance Imaging confirmed the hydrometrocolpos and imperforate hymen. After obtaining informed consent from the family, a vertical incision and annular hymenotomy were done to drain 200mL of milky fluid. A follow-up ultrasound was done to confirm the resolution of HMC and neonate discharge on the 4th day with improvement.Conclusion: A high index of suspicion and immediate postnatal evaluation of neonates presented with prenatal U/S showing intra-abdominal mass will result in early diagnosis and treatment of neonatal hydrometrocolpos before the development of complications.Keywords: Adama, imperforate hymen, neonatal hydrometrocolpos